Digital competence: What makes nurses a ‘big gun’ in the future health industry - Yunus Adhy Prasetyo (Belitung Nursing Journal, 2022)
This letter aims to respond to the editorial’s viewpoint by Aungsuroch, Y. and Gunawan, J. related to nurses’ preparation in the industrial revolution 4.0. Without a doubt, the era of disruption creates massive changes in many sectors, including in the health industry, and nurses are demanded to adopt and adapt to the rapid development of information technology. Therefore, digital competence is highly emphasized as an essential skill for today’s nurse generation in order to be the “big gun” of tomorrow.